Assessment of genetic conservation units of an endangered glacial relict insular species, Amentotaxus formosana, based on fine-scale genetic structures of multiple fragmented mountainous populations in Taiwan - Ko, Ya-Zhu; Shih, Huie-Chuan; Ho, Chin-Shang; Chen, Chaur-Tzuhn; Hsu, Tsai-Wen; Shiao, Meng-Shin; Chiang, Yu-Chung (Frontiers in Plant Science, 2025)
Insular species are usually endemic and prone to long-term population reduction, low genetic diversity, and inbreeding depression, which results in difficulties in species conservation. The situation is even more challenging for the glacial relict species whose habitats are usually fragmented in the mountainous regions. Amentotaxus formosana is an endangered and endemic relict tree species in Taiwan. It is typically found scattered across different mountain regions, leading to fragmented and discontinuous populations in various habitats. Consequently, reproductive isolation may lead to deep and cryptic population structures between and within populations. To test this hypothesis and assess the most effective conservation units for the species, comprehensive genetic analyses were conducted using multiple microsatellite loci to uncover fine-scale population structures in three mountainous regions. In this study, a substantial sample of over 600 individuals, predominantly middle-aged, was collected, representing a majority of the existing individuals in the Chachayalaishan and Dawu habitats. Population genetic structure analyses were conducted using three complementary Bayesian clustering approaches (STRUCTURE, InStruct, and GENELAND) to ensure robust identification of distinct genetic clusters in three key habitats (CHA, DAWU, and DL). Results indicated low genetic diversity, distinct genetic differentiation, and severe inbreeding within fragmented populations. Additionally, demographic analysis suggested a substantial downfall in effective population sizes and limited gene flow within and between populations. Based on these findings, we recommend several management strategies to ensure the effective preservation of A. formosana: (1) establishing genetic conservation units corresponding to distinct genetic clusters in the CHA (CG-8-1 to CG-8-8), DAWU (DG-15-1 to DG-15-15), and DL (LG-6-1 to LG-6-6) populations; (2) implementing interpopulation cross-breeding programs to enhance genetic diversity; (3) promoting habitat restoration efforts to establish connectivity among fragmented populations; and (4) implementing vegetative propagation of selected trees for ex-situ conservation, along with establishing conservation nurseries and seed production areas. These localized conservation approaches, combined with the comprehensive genetic insights provided by this study, serve as crucial directives for the genetic monitoring, policy formulation, and sustainable conservation of A. formosana.